Perbandingan Aktivitas Anti Bakteri Ekstrak Daun Pepaya (Carica Papaya L) Dan Daun Kelor (Moringa Oleifera L) Terhadap Bakteri Staphylococcus Aureus - Abeiasa, M Saka; Gusnelti, Yesi; Warma Putri, Romi Yanti (Jurnal Medisains Kesehatan, 2022)
This study aims to determine the comparison of papaya leaf extract (Caricapaya L) and Moringa leaf (Moringa oleifera L) against staphylococcus aureus bacteria. The type of research used is a laboratory experiment with a completely randomized design (CRD), using the nutrium agar method, namely using disk paper that already contains papaya leaf extract (Carica papaya L.) and Moringa leaf (Moringa oleifera L.) against staphylococcus aureus bacteria. the results of the inhibition zone of papaya leaf bacteria at a concentration of 25-100% experienced ups and downs, at a concentration of 25% with an average inhibition of 5.6mm and at a concentration of 50% increased with an average inhibition of 6mm then at a concentration of 75% decreased with an average of 5.8mm and at a concentration of 100% increased by an average of 6.6mm. Moringa leaves have the inhibitory activity of staphylococcus aureus bacteria from a concentration of 25% to 100% also experience an up and down phase, at a concentration of 25% with an average of 5.6 mm and at a concentration of 50% it increases with an average of 6.2 and at the concentration of 75% also increased with an average of 7 and the concentration of 100% decreased with an average of 6.5 so that Moringa leaves have an antibacterial inhibitory power. There is a difference between papaya leaf extract and Moringa leaf extract, namely at concentrations of 25%, 50% 75% and 100%